2014
DOI: 10.1242/dev.102681
|View full text |Cite
|
Sign up to set email alerts
|

Mll2 is required for H3K4 trimethylation on bivalent promoters in embryonic stem cells, whereas Mll1 is redundant

Abstract: Trimethylation of histone H3 lysine 4 (H3K4me3) at the promoters of actively transcribed genes is a universal epigenetic mark and a key product of Trithorax group action. Here, we show that Mll2, one of the six Set1/Trithorax-type H3K4 methyltransferases in mammals, is required for trimethylation of bivalent promoters in mouse embryonic stem cells. Mll2 is bound to bivalent promoters but also to most active promoters, which do not require Mll2 for H3K4me3 or mRNA expression. By contrast, the Set1 complex (Set1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
235
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(260 citation statements)
references
References 83 publications
24
235
0
1
Order By: Relevance
“…Whereas Mll2 was bound at both bivalent and active promoters, Cxxc1, a Set1 complex subunit, was found only at active gene promoters. Consistent with the findings from Hu et al (2013), Denissov et al (2014) further showed that the induction of genes with bivalent promoters was not influenced by abrogation of Fig. 3.…”
Section: Bivalent Promoters: Inherently Balanced Between Trxg and Pcgsupporting
confidence: 87%
See 2 more Smart Citations
“…Whereas Mll2 was bound at both bivalent and active promoters, Cxxc1, a Set1 complex subunit, was found only at active gene promoters. Consistent with the findings from Hu et al (2013), Denissov et al (2014) further showed that the induction of genes with bivalent promoters was not influenced by abrogation of Fig. 3.…”
Section: Bivalent Promoters: Inherently Balanced Between Trxg and Pcgsupporting
confidence: 87%
“…Given that bivalency has been proposed to poise developmental genes for rapid activation (Voigt et al, 2013), this observation was unexpected and calls into question the function of bivalency. Independent evidence for Mll2 being the bivalent domain H3K4 methyltransferase came in 2014 (Denissov et al, 2014), but, in this study, the authors further examined the interplay between the various Set1/Trithorax-type H3K4 methyltransferases.…”
Section: Bivalent Promoters: Inherently Balanced Between Trxg and Pcgmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of H3K4me1 has been proposed to be a key step in enhancer decommissioning (preprint: Agarwal et al , 2017; Cao et al , 2018; Whyte et al , 2012; Yan et al , 2018), though a direct function for this mark remains controversial (Dorighi et al , 2017; Cao et al , 2018; Yan et al , 2018). Since inactivation of various MLL family members fails to ablate H3K4 methylation at most pluripotency enhancers or alter pluripotency gene expression (Denissov et al , 2014; Wang et al , 2016; Cao et al , 2017, 2018; Dorighi et al , 2017; Yan et al , 2018), the importance of this class of histone modification in regulating the activity of the pluripotency network remains to be stringently tested. Our finding that H3K4me1 becomes undetectable at the Esrrb enhancer in committed cells, coincident with loss of TF binding and gain of DNA methylation, might provide a well‐characterized model to address these controversies.…”
Section: Discussionmentioning
confidence: 99%
“…2E). Interestingly, reanalysis of a published ESC ChIP-Seq dataset on MLL2 (KMT2B) (23) revealed that over 50% of MLL4-independent AEs are also occupied by MLL2. In contrast, only ∼25% of MLL4-dependent AEs are occupied by MLL2 in ESCs (SI Appendix, Fig.…”
Section: Mll4 Is Dispensable For Maintaining Somatic Cell Identity Butmentioning
confidence: 99%